1989
DOI: 10.1007/bf00643520
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-motion electromyographic silent period on dynamic force exertion during a rapid ballistic movement in man

Abstract: The effects of pre-motion silent period (PSP) on dynamic force exertion were studied in ten healthy subjects performing ballistic elbow extensions. The experiments were designed to evaluate the significance of mean differences between the averaged dynamic force curves of two groups: PSP-presence groups and PSP-absence groups. The presence of PSP was judged quantitatively and automatically by means of a newly developed method using statistical analysis. The results indicated that there were two effects of PSP o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 11 publications
5
22
0
Order By: Relevance
“…The incidence of such silent period varied across subjects (range: 7.4-76.8%) at a rate similar (range: 5-60%) to the silent period in the agonist muscle at the transition of a sustained and ballistic contraction (Mortimer et al 1987;Walter 1988;Aoki et al 1989;Van Cutsem and Duchateau 2005). In the two conditions, the variability of silent period incidence among subjects suggests that it is a learned behavior (Nishizono and Kato 1987;Walter 1989;Moritani 1993;cf., however, Mortimer et al 1987;Zehr et al 1997) rather than an automatic component of a movement program.…”
Section: Influence Of Active Antagonist Contraction On the Ballistic mentioning
confidence: 89%
See 2 more Smart Citations
“…The incidence of such silent period varied across subjects (range: 7.4-76.8%) at a rate similar (range: 5-60%) to the silent period in the agonist muscle at the transition of a sustained and ballistic contraction (Mortimer et al 1987;Walter 1988;Aoki et al 1989;Van Cutsem and Duchateau 2005). In the two conditions, the variability of silent period incidence among subjects suggests that it is a learned behavior (Nishizono and Kato 1987;Walter 1989;Moritani 1993;cf., however, Mortimer et al 1987;Zehr et al 1997) rather than an automatic component of a movement program.…”
Section: Influence Of Active Antagonist Contraction On the Ballistic mentioning
confidence: 89%
“…The current results showed that a silent EMG period between the end of the antagonist activity and the onset of the ballistic agonist activity induced by a brief period of relaxation had a similar influence on the rate of torque development than a brief silent period in agonist EMG activity inserted between a sustained and ballistic agonist action. In both conditions, the absence or reduction in EMG activity indicates that most motor neurones innervating both agonist and antagonist muscles are in a resting state before the onset of the ballistic contraction, which enables a briefer agonist activation than during a ballistic contraction superimposed to a sustained submaximal contraction (Conrad et al 1983;Tanii 1984;Mortimer et al 1987;Aoki et al 1989;Van Cutsem and Duchateau 2005). A briefer EMG activity at the onset of a ballistic action is usually accompanied by an increased rate of torque development (Van Cutsem and Duchateau 2005) or speed of movement (Corcos et al 1989).…”
Section: Influence Of Initial Conditions On the Ballistic Contractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a silent period has been observed in learned tasks with sudden force exertion (Laursen et al 1978;Laursen 1984) andpreceding rapid contractions (Yabe 1976;Aoki et al 1989;Wierzbicka et al 1993). Three possible explanations for this phenomenon can be given.…”
Section: Discussionmentioning
confidence: 99%
“…Three possible explanations for this phenomenon can be given. One is that the occurrence of a silent period in the EMG signal prior to activation can be considered a means to interrupt the background activity, hereby synchronising the motor units to exert higher and faster muscle forces (Yabe 1976;Aoki et al 1989;Wierzbicka et al 1993). Secondly, the existence of a silent period causes the muscle force to decline, hereby stretching the muscle before shortening.…”
Section: Discussionmentioning
confidence: 99%